Using Interprofessional Simulation to Enhance Student Knowledge and Promote Collaborative Practice in Disaster Management. (March 2023) - Fifolt, Matthew; Brown, Michelle; Kidd, Elena; Nabavi, Meena; Lee, Heather; McCormick, Lisa C.
Introduction . Experiential learning activities, such as simulations, strengthen student learning by allowing students to apply didactic knowledge to real-world settings. Moreover, simulation-based interprofessional education supports teamwork and skill development as outlined in accreditation standards for many health and health-related academic programs. The purpose of this article is to describe the role of interprofessional simulation in enhancing student knowledge and promoting collaborative practice for disaster management. Method . Multiple data sources were used to assess a simulated EF-5 tornado disaster event including an observational protocol, a disaster simulation survey, and a survey from the Office of Interprofessional Simulation for Innovative Clinical Practice. Results . Students reported increased satisfaction and knowledge with applying skills associated with interprofessional practice, including communication, teamwork, and collaboration. Additionally, students identified skills that could be broadly applied to a range of work settings on graduation such as seeking role clarity, utilizing job action sheets, and responding to a complex situation. Notably, students reported increased levels of knowledge gain of the incident command structure after applying knowledge from didactic sessions to the simulation. Conclusion . Simulation is an innovative strategy for integrating theory and practice to best prepare graduates for the dynamic world in which they live and work. Experiential learning opportunities appeal to the assumptions of adult learning, promote the skills that employers value, and bridge the competencies of multiple academic disciplines that frequently operate in silos. Institutional leaders should view experiential learning as a critical component of student learning and an investment in workforce development.